Mass spectrometry of surfactant aggregates - Ceraulo, Leopoldo; Giorgi, Gianluca; Liveri, Vincenzo Trco; Bongiorno, David; Indelicato, Serena; Di Gaudio, Francesca; Indelicato, Sergio (European journal of mass spectrometry (Chichester, England), 2011)
In contrast with the enormous amount of literature produced during many decades in the field of surfactant aggregation in liquid, liquid crystalline and solid phases, only a few investigations concerning surfactant self- assembling in the gas phase as charged aggregates have been carried out until now. This lack of interest is disappointing in view of the remarkable theoretical and practical importance of the inherent knowledge. The absence of surfactant-solvent interactions makes it easier to study the role of surfactant-surfactant forces in determining their peculiar self-assembling features as well as the ability of these assemblies to incorporate selected solubilizate molecules. Thus, the study of gas-phase surfactant and surfactant-solubilizate aggregates is a research subject which has exciting potential, including mass and energy transport in the atmosphere, origin of life and simulation of supramolecular aggregation in interstellar space. On the other hand, the structural and dynamic properties of surfactant aggregates in the gas phase could be exploited in a number of interesting applications such as atmospheric cleaning agents, transport and protection of pulmonary drugs or biomolecules and as nanoreactors for specialized chemical reactions in confined space. Spectrometric techniques, together with molecular dynamics simulations, have been the principal investigative tools in this field and appearto be particularly suited to gaining fundamental information on the structure and stability of surfactant-based supramolecular aggregates, charge state effects, entrapment of solubilizate molecules, preferential solubilization sites and chemical reactions localized in a single organized aggregate. The main aim of this review is to present the actual state of the art in this novel and exciting research field underlining the knowledge acquired up to now as well as the aspects needing a more deep understanding. Moreover, intriguing departures of the behavior of surfactant solutions under electrospray ionization conditions from that of ionic, polar and apolar analytes will be discussed.